How museum-based creative-product experiences shape cultural confidence via cultural cognition and cultural identity - Xia, Jinjun; Li, Yashi; He, Yuanheng; Ma, Ke (Frontiers in Psychology, 2026)
IntroductionCultural confidence plays an important role in cultural development, social harmony, and personal growth. As living standards improve, demand for cultural and creative tourism products continues to rise because they provide meaningful, place-based experiences in built cultural environments such as museums. Framed within scholarship on people–place bonds, this study examines how cultural and creative tourism product design (CCTPD)—as a cultural communication carrier situated in a museum context—is associated with cultural confidence, and whether these associations are consistent with a sequential pattern involving cultural cognition and cultural identity.MethodsUsing 314 survey responses collected in the Cultural and Creative Experience Pavilion of the Chongqing Three Gorges Museum, structural equation modeling (SEM) tested direct and indirect associations among cultural cognition, cultural identity, and cultural confidence. Given the cross-sectional design, the estimated mediation paths are interpreted as correlational rather than causal. Drawing on the Strategic Experiential Modules (sense, act, think, relate, feel), CCTPD was modeled as a higher-order construct with five first-order dimensions.ResultsSEM results were consistent with a sequential pattern in which cultural cognition was positively associated with cultural identity, which in turn was positively associated with cultural confidence. CCTPD was positively associated with cultural confidence through multiple direct and indirect pathways, with cultural identity serving as a key mediator. Dimension-level analyses indicated that sense, act, and think experiences were associated with cultural cognition; think and relate experiences were associated with cultural identity; and sense, relate, and feel experiences were associated with cultural confidence.DiscussionSituated within a museum as a salient cultural place, the findings suggest that designed place-based experiences may relate to cultural confidence primarily through identity-related processes. Practically, designers and curators can leverage sense/act/think features to suggest cognition, emphasize think/relate to strengthen identity, and activate sense/relate/feel to support confidence—informing environmental psychology, design strategy, and policy/planning for places seeking to nurture identity processes under social and cultural change.